Artificial Intelligence Influence In Education 4.0 To Architecture Cloud Based E-Learning System - Purwono Hendradi; Mohd Khanapi Abd Ghani; S.N Mahfuzah; Uky Yudatama; N Agung Prabowo; R Arri Widyanto (International Journal of Artificial Intelligence Research, 2020)
Business Application Layer in the Architecture of E-learning cloud is an important part, because it is the part that differentiates it from the application of cloud in other fields. The development of education today recognizes the term Education 4.0 which is an adaptation of the Industrial era 4.0 where in this era the role of Artificial Intelligent is important. In this paper the author will review a part of the cloud-based architecture of E-Learning which will correspond with Education 4.0. The aim will be to produce a Cloud-Based E-learning system Architecture design that can be used as a guideline in the direction of Education 4.0.